PENELUSURAN FAKTOR PENYEBAB LONGSOR TEBING TANAH DI GEDANGSARI KLATEN - Endaryanta Endaryanta (Inersia : Jurnal Teknik Sipil dan Arsitektur, 2007)
At a several time later, Indonesia got many disasters. One of it was a landslide disaster at Gedangsari Gunungkidul (near Klaten). This accident occur was caused by water infiltration into the soil that changed characteristic ofsoil,. the shear strength of soil decreased untilpassed the limit ofsafetyfactor, so landslide occurred. This research tries to obtain what caused landslide, because ofinternalfactor, externalfactor and what its cock.